Efficacy and safety of Dexrazoxane (DRZ) in sarcoma patients receiving high cumulative doses of anthracycline therapy – a retrospective study including 32 patients. Issue 1 (December 2016) - Schuler, Markus; Gerdes, Sebastian; West, Antje; Richter, Stephan; Busemann, Christoph; Hentschel, Leopold; Lenz, Felicitas; Kopp, Hans-Georg; Ehninger, Gerhard; Reichardt, Peter; Pink, Daniel
Abstract Background Anthracyclines, as the most effective therapy, are the cornerstone of advanced stage sarcoma treatment. However, anthracyclines can also contribute to myocardial dysfunction and congestive heart failure, ultimately limiting the therapeutic potential of the drug. Coadministration of Dexrazoxane has been shown to effectively reduce cardiotoxicity, however primarily in patients suffering in diseases other than sarcoma. Methods The aim of this retrospective analysis was to evaluate safety and efficacy of chemotherapy with high cumulative doses of anthracyclines in combination with Dexrazoxane. The medical charts of 32 patients treated in four institutions were analyzed. Reasons for coadministration were rechallenge, reaching the cumulative anthracycline dose and preexisting heart failure. Results The median age was 54 years [18–68 years]. The median cumulative anthracycline dose before adding DRZ was 450 mg/m2 and after administration of last anthracycline containing therapy 750 mg/m2 . Either during treatment or follow up, 2/27 patients (7 %) without preexisting major cardiac findings developed anthracycline-induced cardiotoxicity. The median overall survival (OS) from start of the first anthracycline containing chemotherapy was 46 months and 17 months from the initial coadministration of DRZ. At rechallenge, the median progression free survival (PFS) with DRZ was 7 months. In continuous therapy, the median PFS was 13 months from beginning of chemotherapy and 9 months from the addition of DRZ. Conclusion Chemotherapy with high cumulative doses of anthracyclines in addition with DRZ demonstrated a remarkable OS in these advanced disease patients. Cardiac side-effects due to high cumulative doses of anthracyclines requiring discontinuation of anthracycline treatment were rare. A PFS of 9 months from the beginning of the coadministration of DRZ indicates that continuing anthracycline therapy beyond established cumulative doses is a promising therapeutic option.